Calidad de atención y fidelización de los huéspedes del Hotel Dorado Classic en la ciudad de Iquitos, periodo 2023 - Angulo Jaramillo, Alisson Mishel (2024)
This study examined the relationship between service quality and guest loyalty at the Dorado Classic Hotel, Iquitos, during the 2023 period. Utilizing an applied, descriptive-correlational, and non-experimental methodology, responses from 303 guests, selected through probabilistic sampling and employing a questionnaire as the data collection instrument, were analyzed. The results disclosed that service quality, encompassing aspects such as tangible elements, reliability, responsiveness, security, and empathy, significantly influences guest loyalty, with a high degree of satisfaction (60%) and loyalty to the hotel. A strong positive correlation between both variables (Spearman's correlation coefficient of 0.861) was demonstrated, underscoring the importance of exceeding customer expectations to ensure their return and recommendation. This finding highlights the need for the Dorado Classic Hotel to invest in enhancing the quality of its service, staff training, and infrastructure to bolster guest satisfaction and loyalty. The conclusion drawn from the research is that there is a direct and significant relationship between the quality of service and guest loyalty in the hotel context of Iquitos.